2017
DOI: 10.1038/srep44627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GaN/AlGaN/Sputtered AlN nucleation layers on performance of GaN-based ultraviolet light-emitting diodes

Abstract: We report on the demonstration of GaN-based ultraviolet light-emitting diodes (UV LEDs) emitting at 375 nm grown on patterned sapphire substrate (PSS) with in-situ low temperature GaN/AlGaN nucleation layers (NLs) and ex-situ sputtered AlN NL. The threading dislocation (TD) densities in GaN-based UV LEDs with GaN/AlGaN/sputtered AlN NLs were determined by high-resolution X-ray diffraction (XRD) and cross-sectional transmission electron microscopy (TEM), which revealed that the TD density in UV LED with AlGaN N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 46 publications
1
58
0
Order By: Relevance
“…In the results from (102) plane, sample A shows the maximal FWHM of 667 arcsec, and the values of samples B and C significantly decrease to 367 and 337 arcsec. It is well-known that the FWHM values of (002) planes correspond to screw dislocation, and the FWHM values of (102) planes correspond to edge dislocation, respectively [17,18]. The densities of the dislocations can be calculated by [19,20]…”
Section: Resultsmentioning
confidence: 99%
“…In the results from (102) plane, sample A shows the maximal FWHM of 667 arcsec, and the values of samples B and C significantly decrease to 367 and 337 arcsec. It is well-known that the FWHM values of (002) planes correspond to screw dislocation, and the FWHM values of (102) planes correspond to edge dislocation, respectively [17,18]. The densities of the dislocations can be calculated by [19,20]…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we confirmed that small GaN crystals would generate dislocations [ 15 ]. When using metal organic chemical vapor deposition (MOCVD) to grow AlN or GaN NLs, the influences of small GaN crystals become more noteworthy [ 13 , 14 , 16 ]. Compared to MOCVD-grown AlN or GaN NLs, Li-Chuan Chang et al found that the utilization of ex situ sputtered AlN NLs could suppress GaN nucleation on cones and improve the quality of GaN films on PSSs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The EQE equals the multiplication of the internal quantum efficiency (IQE) and the light extraction efficiency (LEE) [6]. Since micro-LEDs are obtained from an identical wafer as large scale LEDs, the fruitful methods for improving IQE of large scale LEDs are also applicable for micro-LEDs [7][8][9][10][11]. However, the ratio of sidewall emitting area to top emitting area is greatly different for micro-LEDs…”
Section: Introductionmentioning
confidence: 99%